All the queen's players [large type] - Feather, Jane (Thorndike Press large print core, 2010)
Rosamund has two loves--sketching and the theater--and is happy to have a brother who indulges her in both. Her idyllic days draw to a close, however, when her cousin, Secretary of State to Queen Elizabeth, deems it time to prepare herself for marriage, and suspects that her eye for art could make her a uniquely valuable spy. Once in the queen's court in the role of a lifetime, Rosamund finds herself not truly prepared for the politics and deceit, nor the love.